2016
DOI: 10.1111/psyp.12652
|View full text |Cite
|
Sign up to set email alerts
|

When rumination counts: Perceived social support and heart rate variability in daily life

Abstract: Rumination and social support could modulate cardiac activity. Although both variables are somehow interrelated, they are often studied independently, and their interplay is seldom considered. We aimed to analyze the interaction of rumination and perceived social support on vagally mediated heart rate variability (HRV) in daily life. The sample consisted of 117 healthy participants (57% female, mean age = 27.9, SD = 5.5 years). Ambulatory HRV (root mean squared successive differences), respiration, body positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 65 publications
1
32
0
1
Order By: Relevance
“…However, it is noteworthy that contact valence was assessed on visual analogue scales and, consequently, negative social interactions, which can have a negative impact on psychobiological stress (e.g.,Friedman et al 2012), could also be assessed and were part of the analyses.5 However, previous studies showed that levels of perceived social support or being engaged in any social interaction during daily life routines can moderate the effects of momentary rumination and depression on heart rate variability (HRV; as another marker associated with the SAM axis)(Gerteis and Schwerdtfeger 2016;Schwerdtfeger and Friedrich-Mai 2009). Given the supposed association of sAA and HRV, these results could be in line with those described in the present work.…”
supporting
confidence: 86%
“…However, it is noteworthy that contact valence was assessed on visual analogue scales and, consequently, negative social interactions, which can have a negative impact on psychobiological stress (e.g.,Friedman et al 2012), could also be assessed and were part of the analyses.5 However, previous studies showed that levels of perceived social support or being engaged in any social interaction during daily life routines can moderate the effects of momentary rumination and depression on heart rate variability (HRV; as another marker associated with the SAM axis)(Gerteis and Schwerdtfeger 2016;Schwerdtfeger and Friedrich-Mai 2009). Given the supposed association of sAA and HRV, these results could be in line with those described in the present work.…”
supporting
confidence: 86%
“…Other stressors that evoke decreases in vmHRV include aversive sounds (i.e., infant crying, violence) (Tkaczyszyn et al, 2013) and emotion-arousing films (Frazier, Strauss, & Steinhauer, 2004). Effects of stress generalize beyond the laboratory context, as increased environmental noise during daily activities is associated with decreases in vmHRV (Kraus et al, 2013) and rumination is associated with reduced vmHRV during unsupportive social interactions (Gerteis & Schwerdtfeger, 2016).…”
Section: Situational Influences On Vmhrv Reactivitymentioning
confidence: 99%
“…An increasing number of studies have documented the reliability and validity of these tools (e.g., Wallén et al, 2012 ; Heathers, 2013 ; Liu et al, 2013 ; Akintola et al, 2016 ). For example, researchers measured participants’ heart rate for 3 weeks with a wearable heart rate monitor and found that individuals’ HRV was affected by the degree of social support they received at that time ( Gerteis and Schwerdtfeger, 2016 ). These results are consistent with earlier laboratory-based studies that observed HRV to be associated with stress (e.g., Shaffer et al, 2014 ) and suggest that measuring physiological responses to real-life events/stimuli is a promising way to estimate consumers’ experience in real life.…”
Section: Physiological and Neuroscientific Measures Used In Consumer mentioning
confidence: 99%